«The human being is the only creature that must be educated». On the relationship between Kant’s education and philosophy of History - Ferreira, Inês Beatriz (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This essay aims to show the dialog that Kant’s suggestions for education establish with his philosophy of History. Starting from the thesis present in the Lessons on pedagogy which suggests that «The human being is the only creature that must be educated», we seek to justify it based on the Kantian concept of Bestimmung, according to which the realization of man’s vocation depends on a permanent effort of an intergenerational nature. Within this framework of ideas, the question concerning education reveals its importance in two senses: both the educational process which is intrinsically presupposed in the pathway towards the integral development of reason and the cultural and civilizational progress, and the educational process in the strict sense, considered as an institutionalized mechanism. On this level, we see Kant reinforcing the urgency of thinking about an educational system in line with the purposes of the human species and therefore reflecting in his suggestions for education – and in its four tasks: to discipline, cultivate, civilize and moralize – the path of maturation of reason in its various stages.